Me seduce mucho, poquito o nada: ilusión e ingenuidad en el pop art de Jules Holland - Tillería, Leopoldo (2025)
This is a journey into the Pop Art of contemporary Dutch visual artist Jules Holland. After observing three of his recent oil paintings, we conclude that the Pop Art/naiveté pairing constitutes the aesthetic foundation of illusion in the European artist’s art. Trompe-l’oeil and the mirror, as resources of this illusion, in addition to the “Kahlo universe” itself, cause Pop Art, post-postmodernism, and reality itself to suffer such an onslaught that contemplating Jules Holland’s works seems like a pure form of play.